THE PROBLEM OF EFFECTIVE PRESSURE ON CONSOLIDATION OF ZIRCONIA NANOPOWDERS AND ITS SOLUTION WITH SPARK-PLASMA SINTERING - Edvin GEVORKYAN; Yury GUTSALENKO; Vladimir CHISHKALA; Olga MELNIK; Maxim KISLITSA (Fiabilitate şi Durabilitate)
The problem of physical and mathematical prediction of rational pressure during sparkplasma sintering of zirconia nanopowder is being considered. The physical aspects of this problem are defined, and it is presented an approach to the calculation of the pressure in the compression cycle at the stage of pre-production and experimental development. The calculation is based on the use of the Paschen law in relation to the considered model of spark plasma consolidate of nanopowders under pressure. The calculation result is compared with the practical experience of energy-saving high-speed spark-plasma sintering of the fine high-density ceramics from (Zr0.94Y0.06)O1.88 nanopowder.